Pengembangan Bahan Ajar Matematika dengan Memanfaatkan Program Geogebra untuk Meningkatkan Kemandirian Belajar - Indri Lestari; Khotimah Khotimah; Eva Fitria Ningsih (Universitas Indraprasta PGRI, 2019)
This research aims to determine the characteristics of the book which is sufficient for improving independence of student learning, especially on functional subject with Geogebra program. The research method used is research and development, where the research is intended to develop and produce certain product, then test the effectiveness of these products. The subjects in this research were students of SMP Negeri 6 Serang City with a limited scale test conducted on 5 students, while field tests were conducted on 15 students. The conclusions obtained in this research are product feasibility test of 78.8% according to experts and students who use teaching materials by utilizing the Geogebra program can improve the self regulated learning compared to the students before using the teaching materials.